Is The Nigerian Stock Market Efficient? Pre and Post 2007-2009 Meltdown Analysis - Nageri, Kamaldeen Ibraheem; Abdulkadir, Rihanat Idowu (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2019)
Efficient market hypothesis asserts movements in asset prices are due to significant changes in information. The financial crisis of 2007-2009 originated from subprime mortgages in the United States and affected African countries through local stock markets. This study evaluates the Nigerian stock market efficiency in the pre and post financial meltdown of 2007-2009. GARCH models under three error distributional assumptions were used. The data covers January 2010 to December 2016 divided into pre and post meltdown. Findings indicate that in the pre and post meltdown, the Nigerian stock market is inefficient in the weak form while using the meltdown as event window, the market is efficient in the semi-strong form. It was recommended that prompt release of financial information by quoted firms should be on-line real time and mandatory to discourage rumour and speculative activities. Authority should not only spell out punishments but should be strict and firm about it.